The SAGE handbook of qualitative research design / edited by Uwe Flick. - Flick, Uwe, 1956- (SAGE Reference, 2022)
Qualitative research design is continually evolving. It is not only more established in disciplines beyond the traditional social sciences in which it is a standard choice, but also just as impacted by the changes in what data, technologies, and approaches researchers are using. This handbook takes readers through the foundational theories, functions, strategies, and approaches to qualitative research design, before showcasing how it negotiates different data and research environments and produces credible, actionable impact beyond the study. Containing contributions from over 90 top scholars from a range of social science disciplines, this handbook is not just an anthology of different qualitative research designs and how/when to use them; it is a complete exploration of how and why these designs are shaped and how, why, and into what they are evolving.